Social Anxiety and Subjective Quality of Life Among Chinese Left-Behind Children: The Mediating Role of Social Support - Yang, Ying; Lu, Xiaozhou (Frontiers in Psychology, 2022)
The issue of left-behind children has become a key focus in China. In this study, we investigate the mediating role of social support between social anxiety and the subjective quality of life among left-behind children in China. (N = 379, Mage = 13.65). A total of 710 junior high school students were recruited using clustering random sampling from five middle schools in China and investigated using the Social Anxiety Scale for Children, Social Support Rating Scale for Adolescents, and Inventory of Subjective Life Quality. The results show that social anxiety is negatively associated with social support and subjective quality of life, and social support is positively correlated with subjective quality of life. In addition, social support partially mediates the relationship between social anxiety and subjective quality of life. In conclusion, these findings provide new insights to improve the subjective quality of life of left-behind children. The focus should be on alleviating social anxiety and increasing social support in order to help left-behind children improve their subjective quality of life.